2015
DOI: 10.1007/s00335-015-9555-1
|View full text |Cite
|
Sign up to set email alerts
|

Utilising the resources of the International Knockout Mouse Consortium: the Australian experience

Abstract: Mouse models play a key role in the understanding gene function, human development and disease. In 2007, the Australian Government provided funding to establish the Monash University embryonic stem cell-to-mouse (ES2M) facility. This was part of the broader Australian Phenomics Network, a national infrastructure initiative aimed at maximising access to global resources for understanding gene function in the mouse. The remit of the ES2M facility is to provide subsidised access for Australian biomedical research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 15 publications
6
15
0
Order By: Relevance
“…Mice with global deletion of Gpr84 (on a C57BL/6 background) were generated. Gpr84 tm1(KOMP)Vlcg targeted embryonic stem cells were obtained from the Knockout Mouse Project (KOMP) repository (University of California‐Davis, Davis, CA, USA), and Gpr84 heterozygous mice were produced, using these cells, by the Australian Phenomics Network (Monash node) (30). Mice were crossed with mice expressing ROSA‐Cre to remove the selection cassette, and the resulting Gpr84 heterozygous pairs were used for subsequent breeding.…”
Section: Methodsmentioning
confidence: 99%
“…Mice with global deletion of Gpr84 (on a C57BL/6 background) were generated. Gpr84 tm1(KOMP)Vlcg targeted embryonic stem cells were obtained from the Knockout Mouse Project (KOMP) repository (University of California‐Davis, Davis, CA, USA), and Gpr84 heterozygous mice were produced, using these cells, by the Australian Phenomics Network (Monash node) (30). Mice were crossed with mice expressing ROSA‐Cre to remove the selection cassette, and the resulting Gpr84 heterozygous pairs were used for subsequent breeding.…”
Section: Methodsmentioning
confidence: 99%
“…The Katnb1 knockout mouse line was generated at the Australian Phenomics Network (APN) Monash University Node using a DEVELOPMENTAL DYNAMICS Taily 2 7 28.9 Katnb1 1/Taily Taily 2 7 28.9 Katnb1 1/Taily EUCOMM KO-first condition ready ES clone (HEPD0636_3_G09) using standard methods (Cotton et al, 2015). To disrupt the Katnb1 gene (ENSMUSG00000031787), the FRT-LacZ-loxP-Neo-FRT-loxP-Katnb1-exon4-loxP cassette was inserted in intron 3 of the Katnb1 gene (Katnb1 tm1a(EUCOMM)Hmgu allele).…”
Section: Generation Of Katnb1 Mouse Linesmentioning
confidence: 99%
“…Based upon past experience and anecdotal evidence that germline transmission may be more difficult to achieve with C57BL/6 ES cells, ES2M staff recommended four ES cell clones per GOI be purchased from EUCOMM ( 35 ). For GOI-1, we found that only one of the four clones passed quality control (two clones had an abnormal karyotype and one clone did not actually contain the tm1a allele).…”
Section: Case Study: Generation Of Two Different Knockout Mouse Linesmentioning
confidence: 99%
“…For GOI-2, only three of four clones were available for shipping and one clone had ≤50% euploidy and therefore failed the necessary criteria for injection ( 35 ). GOI-2 clone #3 was first chosen for microinjection because of its favorable karyotype but failed to produce live births from either injection round.…”
Section: Case Study: Generation Of Two Different Knockout Mouse Linesmentioning
confidence: 99%
See 1 more Smart Citation